A ROOT-based program for analysing T-odd asymmetry results of the neutron-induced fission of heavy nuclei - Berikov, D; Ahmadov, G. S.; Kopatch, Yu. N.; Zhumadilov, K. Sh. (Eurasian Journal of Physics and Functional Materials, 2026)
This paper presents a ROOT based program that allows processing the experimental data on the study of ROT-asymmetry in the angular distribution of fission products and present the results of the experiment in a convenient and visual form. The program can work with huge data sets and detect very subtle e ects. The algorithm used by the program is given in this work. The overall description of the experimental setup, as well as data acquisition and processing systems, are presented, too. Recommended Citation Berikov, D. B.; Ahmadov, G. S.; Kopatch, Yu. N.; and Zhumadilov, K. Sh. (2020) "A ROOT-based program for analysing T-odd asymmetry results of the neutron-induced fission of heavy nuclei," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 2, Article 1. DOI: https://doi.org/10.29317/2020040201